Understanding Consumer Loyalty Through Brand Recognition, Emotional Branding, and Experience: A Study on Kenangan Signature at The Breeze BSD - Yulius, Kevin Gustian; Nugraha, Pamela Florencia; Pramezwary, Amelda (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to analyze the influence of Brand Recognition, Emotional Branding, and Customer Experience on Perceived Value, and their impact on Repurchase Intention among consumers of Kenangan Signature at The Breeze BSD. The research is motivated by the growth of Indonesia’s specialty coffee industry and the differentiation strategy of Kenangan Signature in targeting the upper-middle market segment through a premium customer experience. A quantitative research approach was used, with data collected through surveys using purposive sampling involving 160 respondents who had dined in at Kenangan Signature. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that Brand Recognition, Emotional Branding, and Customer Experience have a positive and significant effect on Perceived Value. Furthermore, Perceived Value has a positive influence on Repurchase Intention. These findings indicate that efforts to strengthen brand recognition, create emotional connections, and provide excellent customer experiences can enhance perceived value, which ultimately drives consumer loyalty and repeat purchase intentions.